2005
DOI: 10.1208/pt060235
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying crystal form content in physical mixtures of (±)-tartaric acid and (+)-tartaric acid using near infrared reflectance spectroscopy

Abstract: The objective of this study was to use diffuse reflectance near infrared spectroscopy (NIRS) to determine racemic compound content in physical mixtures composed primarily of the enantiomorph and to assess the error, instrument reproducibility and limits of detection (LOD) and quantification (LOQ) of the method. Physical mixtures ranging from 0 to 25% (±)−tartaric acid in (+)−tartaric acid were prepared and spectra of the powder samples contained in glass vials were obtained using a Foss NIRSystems Model 5000 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Luner et al [10] investigated that the effect of grinding on the crystal structure of natural tartaric acid. They concluded that there was no major difference between the crystallinity of powder and natural tartaric acid sample and also they observed the natural pattern of tartaric acid.…”
Section: X-ray Diffractometry (Xrd)mentioning
confidence: 99%
“…Luner et al [10] investigated that the effect of grinding on the crystal structure of natural tartaric acid. They concluded that there was no major difference between the crystallinity of powder and natural tartaric acid sample and also they observed the natural pattern of tartaric acid.…”
Section: X-ray Diffractometry (Xrd)mentioning
confidence: 99%
“…The crystallinity of the sample under investigation was comparable with that of a standard XRD profile, although the sample under investigation was more powdery. Literature reports on the effect of grinding on the crystal structure of natural Tartaric acid concluded that particle size of Tartaric acid does not affect the crystallinity of the sample [30] . The XRD profiles observed in literature for the pattern of Tartaric acid were similar to those in this study.…”
Section: Discusionmentioning
confidence: 99%
“…Despite the number of advantages that a green and fast procedure for the enantiomeric excess quantification has, in the literature, the possibility of using NIR or MIR for the quantification of enantiomers in mixture has been described only for a reduced number of compounds of pharmacological interest. In particular, this has been accomplished by means of MIR for mandelic acid and ketoprofen [ 14 ], and by NIR for ibuprofen, epinephrine [ 15 ], and tartaric acid [ 16 ]. In the former case, mandelic acid and ketoprofen were quantified by means of a chemometric regression strategy based on partial least squares (PLS) [ 17 , 18 ] and by exploiting a multivariate curve resolution (MCR).…”
Section: Introductionmentioning
confidence: 99%